Lead Content in Leaves of Wayside Trees on Jalan Sudirman, Bogor - Endes N. Dahlan; Yoyo Ontaryo; Umasda . (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
Because automobiles emitted lead particles, plants grown at various distances from the road can be contaminated by air-borne lead particles. The deposition of lead particles on the leaf surfaces is defined as lead-adsorption and the entrance of lead particles into laaf tissues through stomata is defined as lead-absorption. The amount of Iead-adsorptLon is mearwed in washed-out water, whiie the amount of lead-absorption is measured in washed leaves.The amount of lead-adsorption is less than leadabmrption. Lead-absorption m old leaves iscommonly higher than in young leaves. The plants which belong to the highest class in lead adsopttioa and absorption are : Aidium gua/avc, Tennidia q p r r and Lugerstroemio specha; belonging to the high class is : Swktenia ntacrophylk to the medium class are : Mangifera indica and PterocerpusM a s ; to the low class are : Buuhinia pwpwea and Cmuagium odoratum, and belonging to the lowest class are : Rlicium decipiens, Olnariurn commune, Rcus hirta, Erythrina vanegata and ACP cia mrriculifomis.